Produtividade no Brasil: Uma análise do período recente - Luiz Ricardo Cavalcante; Fernanda de Negri (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The aim of this work is to discuss the recent path followed by the indicators of productivity in Brazil based upon the results obtained in previous analyses and on the collection of additional data on the subject. Initially we discuss the relationship between economic growth and productivity in the approaches which use total and partial measures of productivity. We show that between 30% and 50% of the GDP per capita growth observed in Brazil during the last decade can be credited to the increase of the occupation and participation rates. That explains why the GPD per capita and labor productivity curves detach from each other when plotted in a graph. Based upon this result, we argue that higher rates of growth of the GDP per capita in Brazil can only be obtained if the country reaches higher rates of growth of the labor productivity in the future because significant increases in the employment and participation rates are not expected in the near future. We discuss the results obtained in previous works about the total factor productivity (TFP) in Brazil. We argue that the results are highly sensitive to the production functions, to the parameters and to the data sources used in each model. As a result, there seems to be no consolidated trend to the TFP in Brazil in the recent period. In spite of that, most works tend to suggest higher rates of growth of the TFP in the 2000 (especially after 2003) as compared to the 1990s. [...]
Keywords: O47; 330; productivity; labor productivity; total factor productivity; Brazil; employment rate; participation rate